A Highly Conductive and Hierarchical PANI Micro/nanostructure and Its Supercapacitor Application. (20th December 2016) - Wang, Xinxing; Xu, Ming; Fu, Yunlei; Wang, Shiying; Yang, Tao; Jiao, Kui
Graphical abstract: A 3D hierarchical PANI (H-PANI) was delicately synthesized for supercapacitor applications. The H-PANI has excellent electrical conductivity and unique porous structure. The morphology/structure-related capacitance performance of the H-PANI electrode was studied. This study provides a new perspective for development of PANI for supercapacitor applications. Abstract: Development of three-dimensional (3D) hierarchical micro/nanostructures with large surface area, better permeability and structural stability is an effective strategy for pursuing high performance of supercapacitors. Herein, we report a 3D hierarchical PANI micro/nanostructure (H-PANI) as supercapacitor electrode material. The H-PANI has excellent electrical conductivity and unique porous structure, which could promote rapid charge transfer and ion diffusion. The as-prepared H-PANI electrode shows a relatively high specific capacitance of 520 F g −1 at a current density of 0.5 A g −1 (with a specific capacity of 416 C g −1 for a potential window of 0.8 V), and exhibits excellent rate capability (65% specific capacitance retains from 0.5 to 50 A g −1 ). The electrochemical performance of this hierarchical structured electrode material shows great improvement compared with that of the simple structured PANI prepared in this paper. Notably, the H-PANI was delicately synthesized by simply adjusting the ionic strength and temperature of the regular dilute polymerization reaction system of PANI with no need of any templates or organic structure directing reagents, which made the preparation process simple and low-cost. This study will provide a new perspective for development of much wider variety of PANI materials for supercapacitor applications.